Tundra plant communities along the mesotopographic gradient in NE Finland - Kuusisto, Inka; Huttunen, Sanna; Virtanen, Risto (Wiley, 2025)
In this study, we describe plant communities along the mesotopographic gradient in the low-elevation subcontinental mountains of NE Finland (Utsjoki region). We sampled vascular plants, bryophytes and lichens along 18 mesotopographic ridge-snowbed transects comprising a total of 180 plots. We used non-metric multidimensional scaling (NMDS) ordination with envfit to explore the differentiation of plant communities in relation to mesotopography, elevation, rock cover, cover of bare ground, snowbed size and snowmelt time. The classification of communities was performed using DIANA clustering. Plant communities were differentiated along the mesotopographic gradient, snowmelt time, elevation and rock cover. The DIANA analysis distinguished seven clusters corresponding to the following communities: Betula nana–Lichenes heath, Empetrum–Myrtillus–Stereocaulon heath, Empetrum–Pleurozium–Lichenes heath, graminoid-rich snow-protected heath, Oreojuncus trifidus–Avenella flexuosa snow-protected heath, Polytrichastrum sexangulare–liverwort snowbed, and Salix herbacea–Kiaeria starkei snowbed. Because of the strong impact of snowmelt time on plant community structure and distribution of communities, it is likely that climate change-induced changes in snow conditions are affecting tundra vegetation and especially snowbeds are threatened. Snowbed communities in the Utsjoki region roughly align with previously described vegetation associations of mountain areas in NW Europe. The assignment of the graminoid-rich snow-protected heath community remains uncertain.